The Economies of Scale and Efficiency of Small-Scale Capture Fisheries in Kurau Village, Central Bangka District - Adnan, Nazeli; Bashir, Abdul; Harunurrasyid, Harunurrasyid (Bogor Agricultural University, 2020)
This study investigates the economies of scale and efficiency of small-scale capture fisheries, as well as to know how the socio-economic variable influencing the small-scale capture fisheries business in the Kurau village, Central Bangka district. The approach used is a quantitative method by applying multiple linear regression models to adopt the Cobb-Douglas production function. The study found that the scale-economies condition in the small-scale fisheries is decreasing return to scale. We also found the results of allocative efficiency in this small-scale fisheries business are relatively inefficient. Other findings of model estimation indicated that the variables of capital, labor, and fishing distance have a positive and significant effect, while the variables of age, experience, and education level of fishermen have no significant effect on small-scale fisheries production. The main factor that is an obstacle for local fishermen is technology, therefore technology assistance and support from the government are needed as a policy to improve small-scale capture fisheries business and fishermen welfare.